Mechanical properties and bio activity of titanium hydroxyapatite (Ti-HA) composite coating on 316L-stainless steel substrate prepared by thermal spray / Nurul Humaira Azhar - Azhar, Nurul Humaira (2017)
This study was conducted to investigate the mechanical properties, characterisation and bioactivity of titanium-hydroxyapatite (Ti-HA) composite coated on stainless steel,SS using high velocity oxy-fuel (HVOF) spray technique. Hydroxyapatite, Caio(P04)6(OH)2 was synthesized by using different microwave irradiation that were 800, 900 and 1100 Watts. HA powder was sieved and undergone characterisation and morphology analysis. As the power increased, the peaks for impurities in x-ray diffraction (XRD) pattern decreased and at 1100 W all peaks are seen correspond with standard reference data HA. Meanwhile, field emission scanning electron microscopy (FESEM) morphology of HA powder showed that the HA particles have needle-like shaped and at some places the particles have agglomerated.